Non-Redundant Implicational Base of Many-Valued Context Using SAT - Hidayat, Taufiq; bin Ahmad, Asmala; Ishak bin Desa, Mohammad (COMPUTING AND INFORMATICS, 2021)
Some attribute implications in an implicational base of a derived context of many-valued context can be inferred from some other attribute implications together with its scales. The scales are interpretation of some values in the many-valued context therefore they are a prior or an existing knowledge. In knowledge discovery, the such attribute implications are redundant and cannot be considered as new knowledge. Therefore the attribute implicational should be eliminated. This paper shows that the redundancy problem exists and formalizes a model to check the redundancy.